2012
DOI: 10.1039/c2jm33824f
|View full text |Cite
|
Sign up to set email alerts
|

Hairy polymer nanofibers via self-assembly of block copolymers

Abstract: We demonstrate a simple approach to prepare hairy polymer nanorods/nanofibres by exploiting the self-assembly behavior of block copolymers. The hairy nanofibres were prepared from an asymmetric polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) block copolymer whose self-assembled morphology consisted of PS cylinders dispersed in P4VP matrix. The dissolution of the block copolymer in a P4VP selective solvent resulted in the isolation of individual PS cylinders wrapped with a shell consisting of covalently bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
(33 reference statements)
0
28
0
1
Order By: Relevance
“…The actual morphology for the PS(18500)-b-P4VP(40500) block copolymer, which was mostly used in this work, was confirmed using small angle X-ray scattering (SAXS) and TEM measurements (details in supporting information). The cylindrical domains were subsequently isolated in ethanol as nanofibers on which further sol-gel synthesis of titania shell was done using TTIP as the precursor [23,24]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual morphology for the PS(18500)-b-P4VP(40500) block copolymer, which was mostly used in this work, was confirmed using small angle X-ray scattering (SAXS) and TEM measurements (details in supporting information). The cylindrical domains were subsequently isolated in ethanol as nanofibers on which further sol-gel synthesis of titania shell was done using TTIP as the precursor [23,24]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The important prerequisites here are sufficiently high χN value and strong solvent selectivity towards one of the block. Recently, we have shown that in the case of polystyrene-blockpoly(4-vinylpyridine) (PS-b-P4VP), the core-shell type of hairy nanofibers with PS core and hairy P4VP shell could be easily isolated in a solvent selective for P4VP block and without any additional cross-linking step [23,24]. These nanofibers potentially could be functionalized with a range of functional materials driven by the chemically active nature of the P4VP shell.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Various techniques such as self-assembly, 5 phase separation, 6 drawing, 7 melt bowling, 8 electrospinning, 9 and template-directed synthesis 10 allow for the creation of polymer nanofibrous membranes. Among them, electrospinning has emerged as an attractive nanotechnology for the production of nanofibers for biomimetic tissue scaffolding.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the procedure have been reported in our previous work. [5] Figure 3 shows the TEM image of an isolated single NF with AgNPs incorporated within PS core and the shell composed of collapsed P4VP chains.…”
mentioning
confidence: 99%